The Water-Supply Systems of Nabataean and Roman Ḥumayma - Eadie, John W. (Bulletin of ASOR, 1986)
The only Nabataean settlement of any consequence between Petra and Medaʾ in Ṣāliḥ, Ḥumayma (ancient Auara) became a major station on the Via Nova Traiana after the Roman annexation of Arabia and remained an important garrison-town into the Byzantine period. Although Ḥumayma was the most promising site for settlement in the northern Ḥismā, skillful mobilization of the scarce water resources in this arid zone was required if the inhabitants of the town were to survive and prosper. Previous descriptions of the extensive water system (reservoirs, cisterns, aqueduct) the Nabataeans developed have concentrated on the visible ruins and have had little to say about the relative capacities of the water sources or the pattern of consumption over time. The regional survey we conducted in 1983, on which this article is based, not only produced a more reliable measurement of capacities but also provided an assessment of the strategy of mobilization the inhabitants devised in response to the harsh desert conditions.